Determinants of the Performance of the Schools in Medellin in the High-School Graduation-Year Test (ICFES) - Tobón Orozco, David (Pontificia Universidad Javeriana, 2009)
This paper analyses how the institutional processes, the school management as well as the contexts in which the school and the students are circumscribed, could impact the performance in the high-school graduation-year test (ICFES). A survey was applied with the purpose of know the actions and interactions among educative process actors. Factor Analysis and Hierarchical econometric models were used with the purpose of construct indexes and measure the impact of the considered variables. We found that school level variables, including management, explain a high percentage of the performance variability, while those constructed variables associated to student’s characteristics have a low impact. And parent human capital and the initial student conditions are much more important than the teacher human capital. Contrary to the expected, it’s not clear what kind of use and if to increase infrastructure resources favors the achievement.